Immanuel kant on race mixing: The Gypsies, the black Portuguese, and the jews on St. Thomas - Gorkom, Joris Van. (Journal of the History of Ideas)
What is too often lacking in contemporary interpretations of Immanuel Kant's racial thinking is a more thorough overview of the context and of the literature that he used to support his ideas. This article is mainly limited to Kant's brief discussion on race mixing at the end of this 1785 essay. He presented there the cases of the gypsies, the black Portuguese, and the Jews on St. Thomas in order to show the consequences of this practice. A contextual understanding will reveal how Kant wished to contribute to on-going discussions and how he used his source material.- Reproduced